Effects of corn and molasses supplements with and without feed additives on performance, voluntary intake, and digestive function in cattle fed bermudagrass hay - Balbuena, Osvaldo (1996)
Tesis para obtener el grado de Doctor of Philosophy, de la University of Florida (Estados Unidos), en 1996